Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/anie.200504387
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine in a Native Protein Environment—How the Spatial Demand and Polarity of Fluoroalkyl Groups Affect Protein Folding

Abstract: Give and take: The influence of fluoro substitution of amino acid side chains on their interaction profile in a native polypeptide environment was studied systematically. The fluorination of alkyl groups has opposing electrostatic and steric consequences for the stability of hydrophobic protein cores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
141
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(145 citation statements)
references
References 38 publications
(25 reference statements)
3
141
1
Order By: Relevance
“…Fluorinated amino acids have drawn special attention (4-16) because of the unusual solubility properties of fluorinated hydrocarbons. Several independent studies have shown that fluorination of coiled-coil and helix-bundle proteins leads to enhanced stability with respect to thermal or chemical denaturation (6)(7)(8)(9)(10)(11)(12), an effect attributed to the hyper-hydrophobic and fluorophilic character of fluorinated amino acid side chains.…”
mentioning
confidence: 99%
“…Fluorinated amino acids have drawn special attention (4-16) because of the unusual solubility properties of fluorinated hydrocarbons. Several independent studies have shown that fluorination of coiled-coil and helix-bundle proteins leads to enhanced stability with respect to thermal or chemical denaturation (6)(7)(8)(9)(10)(11)(12), an effect attributed to the hyper-hydrophobic and fluorophilic character of fluorinated amino acid side chains.…”
mentioning
confidence: 99%
“…Although they each contain the same number of hFLeu residues, a 4 F 3 (6-13) and a 4 F 3 (17)(18)(19)(20)(21)(22)(23)(24) are significantly less stable than a 4 F 3 a and a 4 F 3 d. These differences may be explained by vertical packing interactions of the ''b-e'' and ''c-g'' interfaces, the importance of which has been highlighted in studies on other antiparallel coiled-coil proteins. [38][39][40] The knobs-into-holes packing of ''b-e'' and ''c-g'' interfaces for a 4 F 3 a and a 4 F 3 d contain only like residues, in which Leu residues pack exclusively into the vertical hole created by two Leu residues of the adjacent helix and hFLeu residues follow a similar packing arrangement at the opposite interface.…”
Section: Discussionmentioning
confidence: 99%
“…21 The introduction of three hFLeu residues stabilizes the folding of a 4 F 3 d by -8.6 kcal mol À1 relative to a 4 H. For the present studies we initially synthesized three new a 4 variants: a 4 F 3 (6-13), which contains hFLeu in place of Leu at positions 6, 10, and 13; a 4 F 3 (17)(18)(19)(20)(21)(22)(23)(24), which contains hFLeu in place of Leu at positions 17, 20, and 24; and a 4 tbA 6 , which contains the leucine analog b-t-butylalanine in place of Leu at all 6 ''a'' and ''d'' positions.…”
Section: Effect Of Hfleu and Tbala On Stability Of A 4 Proteinsmentioning
confidence: 99%
See 2 more Smart Citations